The complete chloroplast genome sequence of Aristolochia manshuriensis Kom. (Aristolochiaceae) - Kyeonghee Kim; Chae Eun Lim (Mitochondrial DNA. Part B. Resources, 2019)
Aristolochia manshuriensis is a medicinal plant belonging to the family Aristolichiaceae. In this study, complete chloroplast (cp) genome sequence of A. manshuriensis was characterized through de novo assembly with next-generation sequencing data. The cp genome is 160,182 bp long and has a typical quadripartite organization consisting of a large single-copy (LSC), a small single-copy (SSC), and a pair of inverted repeats (IRs). The cp genome harboured 79 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. Phylogenetic analysis revealed that A. manshuriensis has close relationship with Aristolochia macrophylla.